ChemInform Abstract: Three‐Membered Ring Systems. Issue 40 (30th September 2014) - Bergmeier, Stephen C.; Lapinsky, David J.
Abstract Review: advances in the synthesis and reactions of epoxides and aziridines published i2012; 143 refs.